Holocene sediments of the Messina Strait (southern Italy): relationships between source area and depositional basin. (November 2016) - Perri, Francesco; Dominici, Rocco; Le Pera, Emilia; Chiocci, Francesco Latino; Martorelli, Eleonora
Abstract: The Messina Strait, situated along the southern sector of the Italian peninsula, provides a good setting to study the source-to-basin relationships and, thus, the complete transect from continental to deep-marine environments. This work concerns the chemical and mineralogical composition of the fine-grained sediments collected along the Messina Strait, since the distribution of major and trace elements related to the mineralogical assemblages allow us the reconstruction of sedimentary evolution and geological processes affecting the studied sediments and, thus, the relationships developed between source area and sedimentary basin. Studied sediments are very-fine sand, silt and clay mainly phyllosilicates and quartz-bearing. Specifically, sediments located on submerged Calabrian and Sicilian slopes generally show high quartz content, whereas samples of the Calabrian and Sicilian continental slopes generally show high phyllosilicates content. Calcite and feldspars (plagioclase and K-feldspar) occur in different amounts. Few samples contain Fe-oxides. The geochemical signatures of the sediments reflect a provenance from felsic lithotypes. The A-CN-K diagram shows a linear trend parallel to A-CN join reflecting, primarily, weathering from granitoid rocks. This trend may result from non-steady state weathering conditions where active tectonism and uplift, as shown by morpho-structural conditions of the Messina Strait and its complex tectonic network, enhance mechanical erosion of mineralogical zones differentiated along weathering profiles developed on source rocks. Weathering efficiency at source area suggests weak intensity, related to a temperate Mediterranean climate similar to that characterizing the present-day study area. Highlights: Messina Strait is a natural laboratory to study the source-to-basin relationships. We study very-fine sand and silt and clay with sand sediments. The geochemical signatures reflect a provenance from felsic source rocks. Source-area weathering has been interpreted as low-to moderate-intensity. Weathering conditions are related to an active tectonism and uplift.